2015
DOI: 10.21775/cimb.017.023
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ion Channel and Transporter Function Through RNA Editing

Abstract: A large proportion of the recoding events mediated by RNA editing are in mRNAs that encode ion channels and transporters. The effects of these events on protein function have been characterized in only a few cases. In even fewer instances are the mechanistic underpinnings of these effects understood. This review focuses on how RNA editing affects protein function and higher order physiology. In mammals, particular attention is given to the GluA2, an ionotropic glutamate receptor subunit, and K v 1.1, a voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…Interestingly, five variants of the spliced-coding sequence have been found, demonstrating different expression patterns among body parts of the codling moth. Analysis of the CpomTRPA5 mRNA sequence demonstrated the transcript undergoing to mRNA editing by insertion of 15 additional nucleotides within the third exon of the full-length sequence, which is a mechanism occurring for K + channels of multiple organisms, including insects (Holmgren and Rosenthal, 2015). Evolutionary studies suggested the relatedness of TRPA5 gene to the thermal sensor Pyrexia (Peng et al, 2015), which has also been descripted as a thermal-gated K + -channel of insect (Lee et al, 2005).…”
Section: Transient Receptor Potential Channels Of Cydia Pomonellamentioning
confidence: 99%
“…Interestingly, five variants of the spliced-coding sequence have been found, demonstrating different expression patterns among body parts of the codling moth. Analysis of the CpomTRPA5 mRNA sequence demonstrated the transcript undergoing to mRNA editing by insertion of 15 additional nucleotides within the third exon of the full-length sequence, which is a mechanism occurring for K + channels of multiple organisms, including insects (Holmgren and Rosenthal, 2015). Evolutionary studies suggested the relatedness of TRPA5 gene to the thermal sensor Pyrexia (Peng et al, 2015), which has also been descripted as a thermal-gated K + -channel of insect (Lee et al, 2005).…”
Section: Transient Receptor Potential Channels Of Cydia Pomonellamentioning
confidence: 99%
“…Interestingly, five variants of the spliced-coding sequence have been found, demonstrating different expression patterns among body parts of the codling moth. Analysis of the CpomTRPA5 mRNA sequence demonstrated the transcript undergoing to mRNA editing by insertion of 15 additional nucleotides within the third exon of the full-length sequence, which is a mechanism occurring for K + channels of multiple organisms, including insects (Holmgren and Rosenthal, 2015). Evolutionary studies suggested the relatedness of TRPA5 gene to the thermal sensor Pyrexia (Peng et al, 2015), which has also been descripted as a thermal-gated K + -channel of insect (Lee et al, 2005).…”
Section: Transient Receptor Potential Channels Of Cydia Pomonellamentioning
confidence: 99%